Exploration of Antidiabetic Activity of the Whole Plant Extract of Eclipta prostrata by In Silico, In Vitro, and In Vivo Methods - Maniza Muni; Mst. Morsheda Akter Mim; Fahima Aktar; Syeda Sadia Afrin; Safaet Alam; Al Amin Sikder; Jakir Ahmed Chowdhury; Abu Asad Chowdhury; Shaila Kabir; Md. Zakir Sultan; Md. Shah Amran (Avicenna Journal of Medical Biochemistry)
Background: Diabetes is the most common chronic disease worldwide, requiring lifelong medication support. As conventional medications have numerous long-term side effects, herbal drugs, which offer similar effectiveness but fewer complications, are considered an alternative. A common tropical herb, Eclipta prostrata, was tested for its antidiabetic activities.